Bravlin—Brave or Humble? - Vinogradov, Andrey Yu; Korobov, Maksim I. (Slověne, 2017)
The paper focuses on the name of the barbarian warlord that appears in the Slavic and (recently discovered) Armenian versions of the Life of St. Stephen of Sougdaia as Бравлинъ and Պրաւլիս /Praulis/, respectively. These forms seem to point to Πραῦλις or Μπραῦλις in the lost Greek Vorlage. None of the previous attempts at constructing an etymology of the name—Slavic бран(ъ)ливъ (Russian copies of the Life), Swedish Bråvalla (G. Vernadsky, N. Belyaev, and O. Pritsak), Indo-Aryan *pravlīn(а)- (O. Trubachev), Spanish Braulio (V. Vasilievsky), or Gothic *Bra(h)vila (N. Ganina)—may be considered satisfactory. Having revisited the historical and linguistic arguments, we suggest that the name given to the barbarian prince humbled by the miracle of St. Stephen in the Greek text of the Life represented, in fact, good Greek: Πραΰλιος or Πραῦλις (from πραΰς ‘mild, humble’); furthermore, we suggest that the positional voicing of Π- > Μπ- [b] in Late Middle Greek might account for the initial Б-/Պ- (West Armenian [b]) of the attested forms.